Horns, Fangs, and People: Review of Isabelle Mauz, Gens, Cornes et Crocs - Granjou, Céline (Humanimalia, 2015)
Isabelle Mauz, Gens, Cornes et Crocs. Paris: Cemagref, Cirad, Ifremer, Inra, 2005. 255p. € 25.40 pb; € 16.99 pdf; € 16.99 e-pub.